PEDAGOGICAL PRACTICES IN ENVIRONMENTAL EDUCATION BY TEACHERS OF FINAL YEARS OF ELEMENTARY EDUCATION: A SYSTEMATIC REVIEW (VERUM: Journal of Scientific Initiation, 2026)
The various human actions imposed on the environment cause imbalances in ecosystems, harming many species and placing many others at risk of extinction. Environmental Education is fundamental, as it promotes students’ reflection and critical thinking within the school context, a space that enables the re-signification of social values and the construction of civic awareness, which fosters the recognition of the human connection with nature. The objective of this study is to investigate how Environmental Education is developed in the final years of elementary education and how the pedagogical practices employed promote awareness-raising and civic education through a Systematic Literature Review. The material was collected from the Google Scholar, CAPES, BDTD, SciELO, and LILACS databases, with the aim of gathering studies published between 2016 and 2022. The results indicate that teachers use local problems as a way to raise students’ awareness and to interpret global imbalances. The most frequently used resource by teachers in Environmental Education classes is the textbook. Strategies that promoted student autonomy and protagonism contributed to the development of reflective and sensitive individuals. However, for the construction of socio-environmentally responsible citizens, it is necessary that this development be continuous, spanning all levels of education, and that interdisciplinarity across disciplines be ensured by adequately trained professionals.
Keywords: Teaching strategies; Biology teacher education; Teacher training